MINORITY LANGUAGE REVITALIZATION: BETAWINESE AND LAMPUNGNESE CASE STUDY - Imelda; Halimatusa’diah (TALENTA, 2021)
Awareness about the decline of various ethnic cultures in Indonesia has been the government concern since the New Order era (1966-1998). Towards the issues, the Indonesian government has done more concrete actions, i.e., cultural revitalization, including local languages, which began in the second year of the First Five Development Year (Repelita), the 1970s [1]. The same source further explained that there were five main activities to carry on, including (a) language standardization, (b) language socialization, (c) translation, (d) language and literary research, and (e) development of language agents and information networks [1]. Interestingly, (a) the condition of the local language in Indonesia, (b) the shifting factor of the language, and (c) the language revitalizations that have been done are various. The paper will discuss two cases of minority languages revitalization in Indonesia, namely Betawi and Lampung. Both languages are interesting to review and compare since they have the same characteristics: they are the language of minority ethnic groups whose environment is the center of migration of various ethnicities since the Dutch colonial. The massive development of Jakarta has displaced Betawi people to the suburbs, such as Depok, Bekasi and Tangerang (Shahab, 2004: 20). As a consequence, the existence and the role of the Betawi language, which is considered a dialect of Jakarta, is now being eroded (Chaer, 2017: 160). Meanwhile, the Lampungnese region has been the first transmigrant location in the colonial era from Java island, 1905. Currently, Lampungnese is around 11.92 percent [2] of the entire population in the Province and the younger speakers have shifted to Indonesian/Malay. This desk study examines various literature, previous research, and policy papers to present findings regarding the latest report on language revitalization carried out. One of the efforts to revitalize the Betawi language that has been carried out is building Betawi cultural villages in Condet and Setu Babakan [3]. However, the high number of mixed marriages and the dominance of Indonesian made it challenging to transmit local language between generations since younger generations speak Indonesian more often. On the other hand, the Lampung provincial government has made efforts to teach the Lampung language from elementary school to university to produce Lampung language teachers. Unfortunately, the efforts that have been done have not shown better results since younger Lampungneses are more fluent in Indonesian better than Lampungnese.